Ch. R. Zinzendorf: Písně Jednoho pravdivého Milovníka Muk Ježíšových - Putna, Martin C. (Lidé města, 2024)
The first modern edition of Baroque-era publication documenting the influence of Pietist religiousness in the milieu of Czech exiles. Christian Renatus Zinzendorf (1727–1752), the son of the founder of the renewed Unity of the Brethren movement, N. L. Zinzendorf, was an author of a series of songs taking the erotic mysticism of Jesus to the extreme. The Czech exile Zachariáš Jelínek (1714–1763) translated the collection into Czech for the use of the Unity of the Brethren based in Berlin. The edition presents the complete texts of this publication dating from 1758. The commentary hints at the typical characteristics of this religiousness, explains the circumstances of the origins of this almost completely unknown example of exile literature, and describes the principles of language in this edition.